Penerapan SAK EMKM Pada Usaha Mikro, Kecil, dan Menengah: Studi Kasus UMKM Di Kota Tanjungbalai - Utari, Rika; Harahap, Isnaini; Syahbudi, Muhammad (Jurnal Ilmiah Akuntansi Kesatuan, 2022)
This study aims to determine the application of SAK EMKM financial accounting standards to UMKM in the city of Tanjungbalai. This research uses primary and secondary data. In this study, the population is 5,360 UMKM owners and using the Slovin formula in determining informants to be 98 UMKM. While the data in this study were collected using structured interview techniques and questionnaires. The method used is qualitative with a descriptive approach. Based on the results of the analysis, it is known that the implementation of SAK EMKM in the city of Tanjungbalai has not yet fully occurred. Based on the data that has been collected, the obstacle in implementing SAK EMKM is that the preparation of financial reports based on SAK EMKM has a process that requires time, energy and sufficient accounting knowledge for UMKM to apply this standard. So from these obstacles, it is evident from the 98 UMKM studied, only 12 UMKM use these standards.